2016
DOI: 10.19173/irrodl.v17i4.2409
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Access to Higher Education Through Open and Distance Learning: Empirical Findings From Mzuzu University, Malawi

Abstract: Slowly but surely, open and distance learning (ODL) programmes are being regarded as one of the most practical ways that universities across the world are increasingly adopting in order to increase access to university education. Likewise, Mzuzu University (MZUNI) set up the Centre for Open and Distance Learning (CODL) to oversee the running of these programmes in 2011. In this study, we adopted the Transactional Distance Theory (Moore, 1997) to investigate the modes of instructional systems, benefits or oppor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
64
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(71 citation statements)
references
References 28 publications
6
64
0
1
Order By: Relevance
“…The results in Figure 2 revealed that 63% 2 of respondents have a positive perception towards the relevance of social media in the learning process. It is partly known that the positive perception is because of the ability of social media to connect learners and tutors in the learning process beyond traditional classrooms (Bora & Ahmed 2013;Chawinga & Zozie 2016;Jovanovic & Chiong 2012). Social media are readily available and affordable to many surveyed respondents.…”
Section: The Perceived Relevance (Usefulness) Of Social Mediamentioning
confidence: 99%
See 1 more Smart Citation
“…The results in Figure 2 revealed that 63% 2 of respondents have a positive perception towards the relevance of social media in the learning process. It is partly known that the positive perception is because of the ability of social media to connect learners and tutors in the learning process beyond traditional classrooms (Bora & Ahmed 2013;Chawinga & Zozie 2016;Jovanovic & Chiong 2012). Social media are readily available and affordable to many surveyed respondents.…”
Section: The Perceived Relevance (Usefulness) Of Social Mediamentioning
confidence: 99%
“…Furthermore, factors that influence the adoption of social media in the learning process are not universal. Since the use of social media may extend academic discussions (related activities) beyond physical classrooms, they can become a powerful tool in enhancing the goal of the government for increasing enrolment, while enhancing the quality of higher education (Chawinga 2017;Chawinga & Zozie 2016). Therefore, it is important to understand their usefulness and how they can be enhanced in the Tanzanian environment.…”
mentioning
confidence: 99%
“…This is as a result of enrollment expansion characterized by a range of weak inputs such as weak academic preparation for incoming students, lack of financial resources, inadequate teaching staff, poor remuneration of staff, and inadequate staff qualifications (Johanson, Richard, & Shafiq, 2011; United States Agency for International Development [USAID], 2014; Aung & Khaing, 2016).Recent studies show that ICT integration in education through e-learning are facing numerous challenges associated with quality. For example, studies in Kenya confirmed that there are quality issues linked to inadequate ICT and e-learning infrastructure, financial constraints, expensive and inadequate Internet bandwidth, lack of operational e-learning policies, lack of technical skills on e-learning and e-content development by teaching staff, inadequate course support, lack of interest and commitment among the teaching staff, and longer amounts of time required to develop e-learning courses (Tarus, Gichoya,& Muumbo, 2015;Makokha & Mutisya , 2016).A related study (Chawinga, 2016) in Malawi on increasing access to university education through elearning observed that the greatest obstacles to e-learning use were: Lack of academic support (77.6%);Delayed end of semester examination results (75.5%); Class too large (74.3%); Delayed feedback from instructors (72.6%); Failure to find relevant information for studies (67%); Poor learning materials/manuals (33.1%); and Lost assignments and grades (19.5%).In light of all these challenges, it is clear that developing countries still remains behind the great revolution of ICTs in Higher Education. Accordingly, further investigation into e-learning use in Kenya is required in order to fill in this gap of research, and extend the body of existing literature by highlighting major quality determinants in the application of e-learning for teaching and learning.…”
mentioning
confidence: 98%
“…A related study (Chawinga, 2016) in Malawi on increasing access to university education through elearning observed that the greatest obstacles to e-learning use were: Lack of academic support (77.6%);…”
mentioning
confidence: 99%
“…Á síðustu árum hefur í sívaxandi maeli verið litið til möguleika fjarnáms við að veita háskóla-menntun í heimabyggð (Chawinga og Zozie, 2016;Ingi Rúnar Eðvarðsson, 2001;Muhirwa, 2012;OECD, 2015;Rennie, Jóhannesdóttir og Kristinsdóttir, 2011;Tomaney og Wray, 2011;Þóroddur Barnason og Ingi Rúnar Eðvarðsson, 2017;Þuríður J. Jóhannsdóttir, 2010). Þótt fjarnám hafi í upphafi byggst á póstsendingum og síðar sjónvarpsútsendingum hafa taekniframfarir nú gert fjarnemum kleift að horfa á upptökur fyrirlestra, taka þátt í umraeðuhópum á netinu og vinna í rauntíma að verkefnum með samnemendum naer og fjaer (Þóroddur Bjarnason og Brynhildur Þórarinsdóttir, 2018).…”
Section: Svaeðisbundin áHrif Háskólaunclassified